Association between right atrial area measured by echocardiography and prognosis among pulmonary arterial hypertension: a systematic review and meta-analysis. Issue 9 (22nd September 2020) - Liu, Ke; Zhang, Chunhua; Chen, Bingyu; Li, Mingfeng; Zhang, Peican
Abstract : Objective: The purpose of this meta-analysis was to evaluate the association between enlarged right atrial area (RAA), as measured by echocardiography, and prognosis of patients with pulmonary arterial hypertension (PAH). Design: Systematic review and meta-analysis. Data sources: To identify potential publications, a comprehensive literature search through MEDLINE, the Cochrane database and the Embase database was performed up to December 2019. Eligibility criteria for selecting studies: Studies were included if they reported Cox regression based-HRs with 95% CIs for all-cause mortality or composite endpoint consisting of death and PAH-related events for echocardiography measurements of the RAA or the right atrial area index (RAAI) in patients with PAH. Data extraction and synthesis: The unadjusted HR with 95% CI was extracted for the final pooled analysis. A random-effects model was used to determine the value of RAA/RAAI in the prognosis of patients with PAH. The data heterogeneity among the studies was estimated by the I 2 statistic and the Cochran Q-statistic. Results: Twelve studies with a total of 1085 patients with PAH were finally included in the meta-analysis. These studies had a mean follow-up time ranging from 9.2 months to 5.0 years. Their findings showed that patients with PAH with enlarged RAA/RAAI were associated with poor prognosis. The risk of all-cause mortality in patients with PAH was found to statistically increase by 50% for every 5-unit increase in RAA/RAAI (HR 1.50, 95% CI 1.28 to 1.75, p<0.001). Similarly, the risk of the composite endpoint also significantly increased by 53% for every 5-unit increase in RAA/RAAI (HR 1.53, 95% CI 1.23 to 1.89, p<0.001). Subgroup analyses in which the patients were stratified by RAA and RAAI were consistent with the main results. Conclusion: The meta-analysis suggested that enlarged RAA/RAAI were associated with increased risk of poor prognosis in patients with PAH.